2022
DOI: 10.15587/1729-4061.2022.254555
|View full text |Cite
|
Sign up to set email alerts
|

Forming the geometric accuracy and roughness of holes when drilling aircraft structures made from polymeric composite materials

Abstract: The subject of this study is indicators of the quality, geometric accuracy, and roughness of holes in aviation structures (AS) made from polymeric composite materials (PCM) produced by drilling. The indicators of quality, geometric accuracy, and roughness of PCM holes were investigated by using kinematic hole drilling schemes and the creation of PCM chips. A kinematic scheme has been built of the cutting forces operating in PCM when drilling with the distribution of zones from 0° to 360°. Experimental studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 11 publications
0
10
0
2
Order By: Relevance
“…The study of shaping geometric precision, roughness, taperness, and cylindricity of holes in PCM is based on the construction of a kinematic scheme of shaping of drilling zones along the surface of the hole. This scheme is constructed in accordance with the adopted kinematic scheme of interaction of the cutting edges of the drill with the fibers of the PCM filler across the drilling [22]. Fig.…”
Section: The Study Subjectmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of shaping geometric precision, roughness, taperness, and cylindricity of holes in PCM is based on the construction of a kinematic scheme of shaping of drilling zones along the surface of the hole. This scheme is constructed in accordance with the adopted kinematic scheme of interaction of the cutting edges of the drill with the fibers of the PCM filler across the drilling [22]. Fig.…”
Section: The Study Subjectmentioning
confidence: 99%
“…When tensile, normal cutting forces N have the highest values compared to adhesion and tangential forces (N ≥ P adh ). 1 -cutting wedge; 2 -fiber; 3 -matrix; Px, Ru, N -external cutting forces, MPa; P adh , τ -adhesion and adhesion forces between the fiber and the matrix, MPa; d -fiber diameter, mm; V -cutting wedge speed, m/min [22] In the zones of angles j from 90° to 180° and j from 270° to 360°, the normal force N coincides with the force component Px and acts on the displacement of the fiber. Due to the thermal factor of deformation that occurs in the contact zone, the filler fibers are «pulled» from the matrix.…”
Section: The Study Subjectmentioning
confidence: 99%
“…Серед методів механічної обробленні домінуюче місце займає оброблення різанням. При цьому, з точки зору проблеми забезпечення якості необхідно оцінювати не тільки точність розмірів, форм, параметрів мікрорельєфу, але і участь при утворенні ліквідів на поверхнях деталей у вигляді мікрозадирків і мікрочастин як для металевих матеріалів, так і для неметалевих [8,9].…”
Section: рис 1 класифікація фізико-хімічних властивостей і геометричн...unclassified
“…In work [10], the developed ANN used with FEM simulation used in forming process to minimize the process development effort in terms of time and cost. In paper [11], the finite element is adopted to analyze and estimate the main factors, which particularly affect pressure and stresses distribution. Work [12] found that there are several important keys that influence the manufacturing process such as the risk of material failure, shape fulfillments, and variation.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%